DESIGN OF DETECTION DEVICE FOR CU CONTAMINATED WATER USING RED DIODA LASER AND PHOTODIODA SENSOR - Rakhmadi, Frida Agung; Rofikhoh, Siti (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2017)
The research on making detection system of Cu contaminated water based on red diode laser and photodiode sensor has been done. The purpose of this research was to know the characteristic of photodiode sensor, to make and to test the detection system of Cu contaminated water based on red diode laser and photodiode sensor. This research was conducted in five phases: characterization of photodiode sensor, making data acquisition system, processing and analyzing of training sample data, making of the detection system, and implementation of detection system on test samples. The results of research showed that photodiode sensor used in this research has transfer function of Â V = 0,0156 * I + 1,1897 with relation of input-output was very strong (r = 0,989); sensitivity was 0,0156 volts / lux; repeatability was 98,31 %; and saturation for the light intensity 200 lux. Meanwhile, the success rate of detection system implementation on Cu contaminated water was 97,5 %.